2017
DOI: 10.1590/s0004-2803.201700000-22
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TTG Among Children With Chronic Functional Constipation Unresponsive to 6 Weeks of Treatment of Constipation

Abstract: BACKGROUND Celiac disease is a glutten induced enteropathy. Some authors recommended screening celiac in children with constipation. There are studies to evaluate celiac disease in children with constipation. But most of them included children regardless to treatment failure. OBJECTIVE The aim of this study was to evaluate frequency of elevated anti TTG in children with constipation after failure to improve during 6 week of appropriate treatment of constipation. METHODS In this cross sectional study, 550 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
0
0
2
Order By: Relevance
“…In an Italian study it was found in 13% of celiac patients, which is similar to our results of 9% of men and 20% of women [25]. Studies on patients with chronic constipation show high rates of CD in both adults and children [26,27,28]. This finding in our study may be confounded by patient reporting of symptoms leading to recall bias as well as other disorders such as pelvic floor dysfunction and irritable bowel syndrome constipation type which predominate in women.…”
Section: Discussionsupporting
confidence: 89%
“…In an Italian study it was found in 13% of celiac patients, which is similar to our results of 9% of men and 20% of women [25]. Studies on patients with chronic constipation show high rates of CD in both adults and children [26,27,28]. This finding in our study may be confounded by patient reporting of symptoms leading to recall bias as well as other disorders such as pelvic floor dysfunction and irritable bowel syndrome constipation type which predominate in women.…”
Section: Discussionsupporting
confidence: 89%
“…В последние годы многие исследователи уделяют большое внимание кишечному кровотоку, так как от его состояния зависит течение воспалительных процессов и заживление анастомозов после реконструктивных операций на кишечнике. Однако, как говорилось выше, все исследования по определению гемодинамики кишечника в основном проводились в опытах на животных или интраоперационно [13][14][15]. Среди применяемых для этой цели методов исследования следует выделить реографию, которая широко используется для исследования упруго-вязких свойств артериальных сосудов, что дает возможность судить о ходе гемодинамических процессов как в исследуемых органах, так и в целом по регионарному и центральному звеньям кровообращения.…”
Section: результаты и обсуждениеunclassified
“…Исследование уровня антител к тканевой трансглутаминазе показало, что у 42 из 550 (7,6%) имелись повышенные значения. В дальнейшем у 40 из 42 (95%), выявленных при серологическом скрининге, гистологически подтверждена целиакия [23].…”
unclassified